Crystal structure of dimethyl-1κ(2) C-bis(μ-4-methylphenolato-1:2κ(2) O:O)(N,N,N′,N′-tetramethylethylenediamine-2κ(2) N,N′)indium(III)lithium(I) - Briand, Glen G. (Acta Crystallogr E Crystallogr Commun, 2015)
The mixed bimetallic title compound, [InLi(CH(3))(2)(C(7)H(7)O)(2)(C(6)H(16)N(2))] or [(tmeda)Li-μ-(4-MeC(6)H(4)O)(2)InMe(2)] (tmeda is N,N,N′,N′-tetramethylethylenediamine), exhibits a four-membered LiO(2)In ring core via bridging 4-methylphenolate groups. The Li and In atoms are in distorted tetrahedral N(2)O(2) and C(2)O(2) bonding environments, respectively. The Li atom is further chelated by a tmeda group, yielding a spirocyclic structure.